Investments in blood safety improve the availability of blood to underserved areas in a sub‐Saharan African country. (November 2014) - Pitman, J. P.; Wilkinson, R.; Basavaraju, S. V.; von Finckenstein, B.; Smit Sibinga, C.; Marfin, A. A.; Postma, M. J.; Mataranyika, M.; Tobias, J.; Lowrance, D. W.
<x xml:space="preserve">Abstract</x> Background and Objectives Since 2004, several African countries, including Namibia, have received assistance from the U.S. President's Emergency Plan for AIDS Relief (PEPFAR). Gains have been documented in the safety and number of collected units in these countries, but the distribution of blood has not been described. Materials and Methods Nine years of data on blood requests and issues from Namibia were stratified by region to describe temporal and spatial changes in the number and type of blood components issued to Namibian healthcare facilities nationally. Results Between 2004 and 2007 (early years of PEPFAR support) and 2008–2011 (peak years of PEPFAR support), the average number of red cell units issued annually increased by 23.5% in seven densely populated but less‐developed regions in northern Namibia; by 30% in two regions with urban centres; and by 35.1% in four sparsely populated rural regions. Conclusion Investments in blood safety and a policy decision to emphasize distribution of blood to underserved regions improved blood availability in remote rural areas and increased the proportion of units distributed as components. However, disparities persist in the distribution of blood between Namibia's urban and rural regions.